Long‐term (17 Ma) turbidite record of the timing and frequency of large flank collapses of the Canary Islands. (20th August 2014) - Hunt, J. E.; Talling, P. J.; Clare, M. A.; Jarvis, I.; Wynn, R. B.
Abstract Volcaniclastic turbidites on the Madeira Abyssal Plain provide a record of large‐volume volcanic island flank collapses from the Canary Islands. This long‐term record spans 17 Ma, and comprises 125 volcaniclastic beds. Determining the timing, provenance and volumes of these turbidites provides key information about the occurrence of mass wasting from the Canary Islands, especially the western islands of Tenerife, La Palma and El Hierro. These turbidite records demonstrate that landslides often coincide with protracted periods of volcanic edifice growth, suggesting that loading of the volcanic edifices may be a key preconditioning factor for landslide triggers. Furthermore, the last large‐volume failures from Tenerife coincide with explosive volcanism at the end of eruptive cycles. Many large‐volume Canary Island landslides also occurred during periods of warmer and wetter climates associated with sea‐level rise and subsequent highstand. However, these turbidites are not serially dependent and any association with climate or sea level change is not statistically significant.